Preventing violence among gifted and talented students (2016)
The school and the family have great roles to play in preventing violence among gifted and talented students. This paper discusses ways through which parents and teachers of gifted children could help to promote children s emotional well-being and prevent violence in times of trouble. Among others, this can be achieved through helping the children develop necessary skills to manage their feelings, to confront unpleasant or adverse realities, and to acquire greater emotional stability. Especially stress that may be a significant cause of violent behaviour among gifted learners.